Unveiling the path to university students' advocacy intention: exploring the intriguing gender moderation - Abdelhamid K. Abdelmaaboud; Ana Isabel Polo Peña; Abeer A. Mahrous (Journal of Humanities and Applied Social Sciences)
Purpose – This study introduces three variables related to brands that have the potential to enhance university students' advocacy intentions. The research explores how university brand identification, the perceived prestige of the university brand and the social benefits associated with the university brand impact students' advocacy intentions. Additionally, the study examines the moderating role of gender in these relationships. Design/methodology/approach – Cross-sectional surveys of 326 undergraduate students enrolled in a Spanish university, and structural equation modeling was used to test and validate the conceptual model. Findings – The findings from the structural equation modeling indicate that university brand identification, perceived university brand prestige and university brand social benefits significantly influence students' advocacy intentions. Furthermore, the multigroup analysis reveals a gender difference in the factors influencing advocacy intentions. Female students demonstrate significance in all three antecedents, whereas male students only show significance in university brand identification and perceived university brand prestige. Practical implications – The current study's findings provide several insights for higher education institutions in developing enduring and committed relationships with their students. Originality/value – This study offers relevant insights into the body of research on university branding, explaining the students' advocacy intentions through the variables of university brand identification, perceived university brand prestige and university brand social benefits. Also, this study is a novelty in introducing empirical evidence for the importance of the moderating role of students' gender.